The development characteristics and mechanisms of the Xigou debris flow in the Three Gorges Reservoir Region - Dai, Zhenwei; Zhang, Anle; Wang, Shufeng; Fu, Xiaolin; Yang, Longwei; Jiang, Xiannian; Wang, Heng (Frontiers in Earth Science, 2023)
Debris flow is a common geological hazard in mountainous areas of China, often causing secondary disasters and seriously threatening residents and infrastructure. This paper uses the Xigou debris flow in the Three Gorges Reservoir Region (TGRR) as an example case study, the development characteristics and initiation pattern of which were analyzed based on field investigation. The disaster dynamics software DAN-W was then used to simulate the entire initiation-movement-accumulation process of the debris flow and conduct the debris flow dynamics analysis. The paper also simulated and predicted the movements of landslides in the formation area of a debris flow after its initiation. The results show that the movement duration of the Xigou debris flow was approximately 40 s, the maximum velocity was 37.1 m/s, the maximum thickness of the accumulation was 18.7 m, and the farthest movement distance was 930 m, which are consistent with the field investigation. When the volumes of landslide transformed into a new source material of debris flow are 5×104, 10×104, 15×104, 20×104, and 26×104 m3, the movement distances of the debris flows are 250 m, 280 m, 300 m, 340 m, and 375 m, respectively. When the volume of the source material exceeds 20×104 m3, debris flow movement can seriously impact the residential houses at the entrance of the gully. This paper can provide a scientific basis for the prevention and mitigation of the Xigou debris flow.